UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI MASALAH KENAKALAN SISWA DI SMA NEGERI 2 WOHA - Irwan Irwan; Rini Purnama (Fitrah, 2022)
This study aims to find out how forms of student delinquency can harm themselves and the school. Knowing the factors that influence student delinquency at SMAN 2 Woha and how the efforts of Islamic Religious Education teachers deal with student delinquency at SMAN 2 Woha. This research is a descriptive qualitative research, namely research that has the aim of understanding the phenomena experienced by research subjects, for example behavior, perceptions and actions. Data collection techniques in the form of observation methods, interview methods / interviews, documentation methods. Data analysis techniques are interviews, reduction, display and triangulation. The results of this study indicate that the forms of student delinquency at SMAN 2 Woha are skipping school or not going to school without explanation, damaging and contaminating school items or facilities, stealing the property of friends and fighting with friends at school and then inviting members from outside. The results of this study indicate that (1) There are several forms of efforts made by Islamic Religious Education teachers in overcoming student delinquency, namely collaborating with BK teachers, student assistants, homeroom teachers and school principals with three phases, the first is preventive action, the second is repressive and the third is curative . (2) There are several factors that support the efforts of the PAI teacher, including the existence of good cooperation that exists between parents of students and teachers (the school). The role of parents is very large for the achievement of the efforts made by PAI teachers. While the factors that hinder PAI teachers in their efforts to overcome student delinquency include the lack of awareness of students to comply with school regulations and the lack of supervision from parents regarding student association.